Association of Step Width with Accelerated Sprinting Performance and Ground Reaction Force - Nagahara, Ryu; Mizutani, Mirai; Matsuo, Akifumi; Kanehisa, Hiroaki; Fukunaga, Tetsuo (International Journal of Sports Medicine, 2017)
This study aimed to describe changes in step width (SW) during accelerated sprinting, and to clarify the relationship of SW with sprinting performance and ground reaction forces. 17 male athletes performed maximal-effort 60 m sprints. The SW and other spatiotemporal variables, as well as ground reaction impulses, over a 52 m distance were calculated. Average values for each 4 steps during acceleration were calculated to examine relationships among variables in different sections. The SW rapidly decreased up to the 13th step and slightly afterward during accelerated sprinting, showing a bilinear phase profile. The ratio of SW to the stature was significantly correlated with running speed based on average values over the 52 m distance and in the 9th–12th step section during accelerated sprinting. The SW ratio positively correlated with medial, lateral and mediolateral impulses in all step sections, except for medial impulse in the 17th–20th step section. These results indicate the importance of wider SW for better sprinting performance, especially in the 9th–12th step section. Moreover, the wider SW was associated with larger medial impulse and smaller lateral impulse, suggesting that a wide SW contributes to the production of greater mediolateral body velocity during accelerated sprinting.
Keywords: mediolateral; running; impulse; foot placement